Pelatihan Analisis Media Digital Menggunakan Tools Pada Media Digital Majelis Ulama Indonesia Kelurahan Pataruman Kecamatan Tarogong Kidul Kabupaten Garut - Milyane, Tita Melia; Widiastuti, Nela (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Digital media is a necessity in the current era of globalization. All sectors of organizational life, individuals and groups, need and use digital media as a daily activity. The massive use of digital media is accompanied by its main functions for organizations, namely spreading messages, and managing and processing messages. The effectiveness of messages disseminated through digital media needs to be measured so that it can be seen whether the message delivered reaches the target, and how effective the message is. In this case, the Indonesian Ulema Council (MUI) is an organization that uses digital media in its organizational activities. The importance of knowing and analyzing digital media will make the organization know the message is well on target. For this reason, our community service team conducted digital media analysis training activities using tools on digital media of the Indonesian Ulama Council, Pataruman Village, Tarogong Kidul District, Garut Regency with the aim that MUI management has the ability to analyze digital media. The method used in this community service activity is training on mentoring the ability to analyze digital media owned by MUI in the Pataruman Village, where this training is carried out for 3 days. The training participants were all MUI administrators (target communities). The result of this activity is an increase in the ability of target community participants to analyze their digital media. The purpose of this activity is to increase the ability and skills of the target community in analyzing and managing their digital media. The end result of this activity is a change in the skills and abilities of the target community in managing their digital media so that they can measure and know how to convey messages effectively and efficiently. The outputs of this activity are broadcasts on YouTube, digital mass media publications, power point materials, and publications in national journals.